Associations of lower-limb muscle strength performance with static and dynamic balance control among older adults in Taiwan - Yeh, Ping-Chun; Syu, De-Kai; Ho, Chien-Chang; Lee, Tian-Shyug (Frontiers in Public Health, 2024)
Background: Aging is an inevitable process of life development. These physical changes can cause a decline in the functional adaptability and health status of elderly individuals.The purpose of this study was to investigate the association of lower-limb muscle strength performance with static and dynamic balance control among older adults in Taiwan.: We conducted a cross-sectional study and reviewed data derived from the National Physical Fitness Survey in Taiwan 2015-2016. A total of 20,846 Taiwanese elderly individuals aged 65 years old or older were recruited as study participants. Demographic characteristics, anthropometric assessments, lifestyle habits, and health-related physical fitness measurements from this dataset were analyzed using the chi-square test, one-way analysis of variance, and linear regression analysis. Lower-limb muscle strength performance was classified into 4 groups based on quartile (Quartile 1 [Q1], Quartile 2 [Q2], Quartile 3 [Q3], and Quartile 4 [Q4]) values.Results: Increased lower-limb muscle strength levels were significantly associated with static balance in men (Q2: β = 2.539, p < 0.